(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
Religion has become a major extra-scientific interest of contemporary natural scientists. The topic permeates the discourse of some of the best known names in comtemporary science, including R. Dawkins, J. Lennox, F. Collins, and S. Gould. These scientists’ attitudes towards religion range from the view that science and religion are mutually exclusive and in conflict through the view that they are discrete fields without overlap to the view that they have to respect each other, engage in dialogue, and cooperate. One may discern in these approaches a number of discursive types: conflictual, integrative, dialogical, pluriperspectival, and discrete. These discourses unfold within the horizons of the epistemological constellations of evolutionism, creationism, intelligent design, and BioLogos. This paper has two main parts. The first part includes a treatment of key issues for understanding the relationship of science to religion: the question of evolutionism and, consequently, the theory of evolution, its scientific status, and its reception by theistic scientists; the attempt to establish a universal natural scientific epistemology and responses to it; and questions of the stochatic nature of the creation of the world and the origin of life. The second part includes consideration of the issue of theistic evolutionism and its major characteristics, followed by an exposition of the views of Christianity or more precisely of the Catholic Church regarding the theory of evolution and an investigation of certain echoes of its theistic reception.